A second-generation ligand for the enantioselective rhodium-catalyzed addition of arylboronic acids to alkenylazaarenes - Roy, Iain D.; Burns, Alan R.; Pattison, Graham; Michel, Boris; Parker, Alexandra J.; Lam, Hon Wai (Royal Society of Chemistry, 2014)
A 2,4,6-trialkylanilide-containing chiral diene has been identified as a superior ligand for the enantioselective rhodiumcatalyzed arylation of alkenylazaarenes with arylboronic acids.